(untitled) (The GIST, 2022)
This research is entitled “An Analysis of Moral Values in the film Hafalan Shalat Delisa: Sociology of Literature Approach". This study aims to describe the moral values reflected in the film Hafalan Shalat Delisa by Sony Gaokasak. This study uses a qualitative descriptive method with a sociology of literature approach. Qualitative research is research that intends to understand the phenomena of what is experienced by research subjects such as behavior, perceptions, motivations, actions and others by means of descriptions in the form of words and language, in a special natural context and by utilizing various scientific methods. . The source of data in this study is the film Hafalan Shalat Delisa by Sony Gaokasak. In this study, data collection techniques were carried out by means of observation, namely direct observation to obtain information. Based on data analysis, this research produces moral values, namely: 1) curiosity, 2) honesty, 3) hard work, 4) discipline, 5) problem solving, 6) commitment, 7) courtesy, 8) Peace-loving, 9) loyalty, 10) helpful, 11) empathy, 12) cooperative, 13) independent and confident, and 14) social care.